2019
DOI: 10.1159/000503629
|View full text |Cite
|
Sign up to set email alerts
|

Association between Irritable Bowel Syndrome and Allergic Diseases: To Make a Case for Aeroallergen

Abstract: Irritable bowel syndrome (IBS) is a functional gastrointestinal disease and the most common cause of prolonged abdominal pain and bowel disturbances in the developed world. While initially thought to be functional or psychosomatic in nature, IBS is now recognized as a heterogeneous group of conditions. A subset of IBS patients and patients with allergic diseases share some characteristic inflammatory features. In fact, atopic children show an increased likelihood of developing IBS as adults. Given these findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 103 publications
1
20
0
Order By: Relevance
“…IBS can overlap with non-celiac gluten sensitivity, with controlled studies showing an improvement of patients after the dietary exclusion of wheat [37]. Interestingly, children with atopic disease are at greater risk of developing IBS than non-atopic children [185]. A subset of patients with IBS have positive colonoscopic food allergen provocation with localized mucosal wheal and flare reactions [186] and the improvement of symptoms with cromoglycates [187], suggesting a potential role of food allergens in the pathogenesis of IBS.…”
Section: Role Of Food Allergens In Other Common Pediatric Gastrointesmentioning
confidence: 99%
“…IBS can overlap with non-celiac gluten sensitivity, with controlled studies showing an improvement of patients after the dietary exclusion of wheat [37]. Interestingly, children with atopic disease are at greater risk of developing IBS than non-atopic children [185]. A subset of patients with IBS have positive colonoscopic food allergen provocation with localized mucosal wheal and flare reactions [186] and the improvement of symptoms with cromoglycates [187], suggesting a potential role of food allergens in the pathogenesis of IBS.…”
Section: Role Of Food Allergens In Other Common Pediatric Gastrointesmentioning
confidence: 99%
“…The relationship between food allergies and recurrent abdominal pain, IBS in particular, has also been widely explored. 92 Some studies have shown an improvement in the severity and the frequency of pain in pediatric patients under fermentable oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAPs) exclusive-regime. 93 In addition, the role of food on their symptoms is often expressed by IBS patients, whether they are adults or children.…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
“…Most, but not all, studies have shown an association between FAPDs and allergic conditions [ 58 ]. FD and functional abdominal pain have been associated with asthma in adolescents [ 58 ].…”
Section: Allergy and Functional Abdominal Pain Disordersmentioning
confidence: 99%
“…Most, but not all, studies have shown an association between FAPDs and allergic conditions [ 58 ]. FD and functional abdominal pain have been associated with asthma in adolescents [ 58 ]. Likewise, asthma and food allergy, allergic rhinitis, and eczema have been associated with FAPDs in adults [ 59 , 60 , 61 , 62 , 63 , 64 ].…”
Section: Allergy and Functional Abdominal Pain Disordersmentioning
confidence: 99%
See 1 more Smart Citation